The Moderating Effect of Monitoring on The Relationship Between Adverse Selection and Decision-Making Involving Escalation Situations: An Experimental Study - Rohma, Frida Fanani; Fitriyah, Anik; Zulfatillah, Auliya (Klabat Accounting Review, 2024)
The streams of research on adverse selection and escalation of commitment are still inconclusive and limited by only manipulating adverse selection in 2 conditions, namely the presence and absence of adverse selection. Meanwhile, the literature shows that adverse selection will always exist in agency contracts even though the information asymmetry mechanism has been modified. This study considers adverse selection manipulation into two levels: high and low. This research investigates the moderating effect of supervision on the impact of adverse selection and commitment escalation. This research used an experimental method with a 2 x 2 factorial design between subjects. This study involved undergraduate accounting students as extension practitioners. The test results show that different levels of adverse selection impact levels of commitment escalation. The research also indicates that supervision is quite effective in filtering the impact of adverse selection on commitment escalation behavior